Autophosphorylation-induced self-assembly and STIL-dependent reinforcement underlie Plk4's ring-to-dot localization conversion around a human centriole. Issue 24 (16th December 2020) - Park, Jung-Eun; Meng, Lingjun; Ryu, Eun Kyoung; Nagashima, Kunio; Baxa, Ulrich; Bang, Jeong Kyu; Lee, Kyung S.
ABSTRACT: Polo-like kinase 4 (Plk4) is a key regulator of centriole biogenesis. Studies have shown that Plk4 undergoes dynamic relocalization from a ring-like pattern around a centriole to a dot-like morphology at the procentriole assembly site and this event is central for inducing centriole biogenesis. However, the detailed mechanisms underlying Plk4's capacity to drive its symmetry-breaking ring-to-dot relocalization remain largely unknown. Here, we showed that Plk4 self-initiates this process in an autophosphorylation–dependent manner and that STIL, its downstream target, is not required for this event. Time-dependent analyses with mEOS-fused photoconvertible Plk4 revealed that a portion of ring-state Plk4 acquires a capacity, presumably through autophosphorylation, to linger around a centriole, ultimately generating a dot-state morphology. Interestingly, Plk4 WT, but not its catalytically inactive mutant, showed the ability to form a nanoscale spherical assembly in the cytosol of human cells or heterologous E. coli, demonstrating its autophosphorylation-dependent self-organizing capacity. At the biochemical level, Plk4 – unlike its N-terminal βTrCP degron motif – robustly autophosphorylated the PC3 SSTT motif within its C-terminal cryptic polo-box, an event critical for inducing its physical clustering. Additional in vivo experiments showed that although STIL was not required for Plk4's initial ring-to-dot conversion, coexpressed STIL greatly enhanced Plk4's ability to generate a spherical condensate and recruit Sas6, a major component of the centriolar cartwheel structure. We propose that Plk4's autophosphorylation-induced clustering is sufficient to induce its ring-to-dot localization conversion and that subsequently recruited STIL potentiates this process to generate a procentriole assembly body critical for Plk4-dependent centriole biogenesis.